Whole-rock and mineral chemistry of magmatic rocks from the Nangqian basin (Eastern Tibet) - Fanny Goussin; Carole Cordier; Nicolas Riel; Stéphane Guillot; Philippe Boulvais; Pierrick Roperch; Anne Replumaz; Karel Schulmann; Guillaume Dupont-Nivet; Filipe Rosas; Guo Zhaojie (PANGAEA, 2020)
This dataset reports major and trace elements, Sr and Nd isotopic ratios, carbonate C and O isotopic ratios, and mineral chemistry of Eocene (~35 Ma) magmatic rocks from the Nangqian basin, Eastern Qiangtang, Central Tibet. Samples have microlithic to microphaneritic porphyritic textures. Trachydacites show K-feldspar, plagioclase and amphibole phenocrysts in a matrix of feldspar + amphibole + biotite + quartz + oxides; tranchyandesites show clinopyroxene, apatite and resorbed biotite phenocrysts in a matrix of feldspar + clinopyroxene + oxides. One intrusive outcrop of porphyritic syenite was also sampled, composed of clinopyroxene and biotite phenocrysts in a matrix of feldspar + clinopyroxene + biotite + apatite + oxides. Whole-rock major and trace elements were measured at ISTerre, University Grenoble Alpes. The SARM-CRPG in Nancy and SEDISOR in Brest performed the whole-rock Sr and Nd isotope analyses. In-situ major-element compositions of mineral phases were obtained using the JEOL JXA-8230 Electron Microprobe at ISTerre, University Grenoble Alpes. Stable isotope analysis of carbonates was carried out in the stable isotope laboratory of Geoscience Rennes, CNRS-University of Rennes I. These geochemical data suggest that the source of the Eocene magmas in Nangqian was a H2O- and CO2-enriched lithospheric mantle. A full discussion of the results can be found in the related article.